Peran Kepuasan Memediasi Pengaruh Kualitas Pelayanan terhadap Loyalitas Nasabah - Kusuma Dewi, Kadek Sintya; Susanti, Putu Herny; Wulandari, Ni Luh Adisti Abiyoga (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Notary Office and PPAT Ni Kade Arini, SH., M.Kn is a professional agency engaged in the field of law in the field of community services, which collaborates with several companies such as private banks and state-owned banks and also serves the needs of individual communities or public customers . This study aims to determine the effect of satisfaction on job satisfaction, to determine the partial effect of satisfaction and job satisfaction on customer loyalty and to determine the indirect effect of satisfaction on customer loyalty through job satisfaction. The population in the study was 632 customers. Determination of the sample using purposive sampling technique is a technique of determining the sample with certain considerations. The research method used is quantitative. The data analysis technique used in this study is the validity test, reliability test, and sobel test. From the results of the study it can be seen that service quality has a positive and significant effect on job satisfaction, satisfaction has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer loyalty and service quality has an indirect effect on customer loyalty through job satisfaction.